Becoming Socrates : Political Philosophy in Plato's "Parmenides" - Priou, Alex (Book collections on Project MUSE., 2018)
"A rigorous investigation of Socrates' early education, pinpointing the thought that led Socrates to turn from natural science to the study of morality, ethics, and politics"--Publisher.